Mongolia’s EPA with Japan: Implementation Progress and Challenges (Mongolian Journal of International Affairs, 2025)
Mongolia first signed an Economic Partnership Agreement (EPA) with Japan, its third neighbor, major investor, and key strategic partner, in 2016, and subsequently joined the Asia-Pacific Trade Agreement in 2021. Currently, discussions are underway to conclude an Economic Partnership Agreement (EPA) with the Republic of Korea and an interim agreement on the Eurasian Economic Union. Although Mongolia has the resources to use such international and interstate agreements, the lack of industrial development limits the possibility of implementing such agreements. Since the establishment of the Mongolia-Japan Economic Partnership Agreement, the trade deficit between Mongolia and Japan has not decreased but has increased year by year, reflecting that the main obstacle facing Mongolia in expanding trade with Japan is the issue of transportation costs. The two sides have been regularly discussing the opportunities and challenges to increase the benefits of the agreement, which is the source of the successful implementation of this agreement in the future. In line with the process in this article, an attempt has been made to analyze the current status and future trend, common challenges, and implications of the Economic Partnership Agreement (EPA) with a third neighbor, Japan.